Development and optimization of climate- and energy related models in electromobility using thermal comfort and CFD - Löseth, Ola (My University, 2022)
Increasing environmental pressure on the automotive industry has resulted in growing efforts to develop sustainable alternatives, among them electric vehicles. Climatization of electric vehicles has been shown to be energy intensive as electric motors do not produce much waste heat. As a result, optimizing the cabin climatization is of great importance, and the purpose of this thesis project is to provide a method capable of evaluating the climate of a vehicle cabin. This project is in collaboration with CEVT, an innovation center that is strongly connected to the vehicle industry. The objective of the thesis is to develop a method that, with the utilization of computational fluid dynamics and thermal comfort modeling, can evaluate the cabin climate to enable energy optimization of the thermal system. The method is developed by utilizing and combining CFD and thermal solvers with the Berkeley Comfort Model to build a virtual cabin environment that can predict the thermal comfort of cabin occupants. The cabin model is also integrated into a system simulation environment representative of the complete vehicle thermal system. The project resulted in a simulation environment capable of assessing the thermal comfort of passengers occupying the vehicle cabin. Furthermore, the study has indicated that the climatization process can be adjusted based on the clothing of the passengers to obtain a significant decrease in energy use.
Keywords: climatization; electric vehicle; CEVT; cabin climate; modeling; CFD; heat transfer; Berkeley Comfort Model; thermal comfort